PENENTUAN PARAMETER ADSORPSI SILIKA SINTETIK DARI CANGKANG KELAPA SAWIT TERHADAP KANDUNGAN AMMONIUM PADA LIMBAH CAIR TAHU - Rizki Karimullah; Rina Elvia; Hermansyah Amir (ALOTROP, 2018)
[DETERMINATION OF SYNTHETIC SILICA ADSORPTION PARAMETERS OF OIL PALM SHELLS AGAINST THE CONTENT OF AMMONIUM ON LIQUID TOFU WASTE] This research aims to determine adsorption capacity of synthetic silica synthesized from Palm Oil (Elaeis guineensis Jacq) shells ashes against the content of Ammonium on tofu liquid waste . The shell sample soaked in a solution of HCl 10% for 2 hours, charred at a temperature of  300 °C for 3 hours ago ashed at 600 °C for 2 hours. Then ash soaked with HCl 1.2 M for 24 hours.  Taken 120 g of ash shells and then mixed right while heated with 160 mL 4 M NaOH. The residue obtained is heated at a temperature of 5000 °C  for 30 minutes, cooled to room temperature and retrieved the Na2SiO3 particle.The particle then  dissolved into 200 ml aquademin and settled at 12 hours, filtered and filtratnya ditetesi with HCL 1 M while stirring, until the white gel is formed and settled in the next 24 hours, filtered, and dried at a temperature of 120 °C for 2 hours, an silica powder obtained as result.  Ammonium Adsorption is done with mass variation 0125, 0.25, 0.5, 0.75, and 1 g silica as well as variations of the contact time of 15, 30, 60, 90, and 120 minutes. The results showed Ammonium adsorption at tofu liquid waste by silica synthesis from the Palm Oil shell ashes occurs with a maximum mass of 0.25 g and optimum contact time of 30 minutes with a capacity of adsorption of 2.581 mg/L and 3,154 mg/L as well as with adsorption efficiency at  61.9% and 76.8%.